Investigation of Occupational Burnout Levels of Physical Education and Sports Teachers in Terms of Various Factors: The Case of Bayburt and Gümüşhane Provinces - İsmail Karataş and Taner Bozkuş (Journal of Educational Issues, 2024)
This research examines the occupational burnout levels of physical education and sports teachers in terms of various factors. In this context, the general survey model, which is consistent with the main purpose of the study, is used in this quantitative study. The survey pool of the research consists of a total of 67 physical education and sports teachers, 5 females and 62 males, working in Bayburt and Gümüşhane provinces. Convenience sampling method, one of the non-probability sampling approaches, is used in the selection of the research group. Data collection tool is a questionnaire form which consists of two parts. In the first part of the questionnaire, there is the “Personal Information Form”, and in the second part, there is the “Maslach Burnout Inventory-Educator Form”. Difference and correlation tests are used in statistical evaluations. Accordingly, significant differences are present in the factors of gender, perceived welfare level and exercise status. However, within the scope of marital status, status of being a manager at the current school, current level of duty, location of the current school, perceived personal income level, perceived family income level (including personal income), active sports status and the type of the active sport, there is no significant difference in the sub-dimensions of the scale. However, the research concludes that there are positive and significant relationships between the participants’ total years of service in the teaching profession and the mean scores of the sub-dimensions of emotional exhaustion and depersonalization. On the other hand, there is no significant relationship between the factors of age and years of service in the teaching profession for the school where they are currently employed, and the sub-dimensions of the scale. As a result, occupational burnout levels of physical education and sports teachers within the scope of various factors are described as they exist.